EXPLAINING DECISION‐MAKING IN GOVERNMENT: THE NEO‐DURKHEIMIAN INSTITUTIONAL FRAMEWORK. (22nd July 2013) - 6, PERRI
<x xml:space="preserve">Abstract</x> In understanding styles of political judgement in government decision‐making, explanatory limitations of rational choice, prospect theoretic, historical institutional, groupthink, and other approaches suggest that there is space for developing other frameworks. This article argues that the neo‐Durkheimian institutional theoretical framework deserves serious consideration. It shows that it offers a powerful causally explanatory framework for generating theories of decision‐making in government which can be examined using historical comparative research designs. The value of the concept of a 'thought style' for understanding political judgement is demonstrated, and contrasted sharply with ideology. The theory argues that informal institutions explain thought styles. Well‐known cases from the Cuban missile crisis, and the Wilson and Heath governments illustrate the argument. The article rebuts criticisms offered of the neo‐Durkheimian institutional framework in the literature. Finally, it identifies recent developments and innovations in the approach that make it especially suited to explaining political judgement in government decision‐making.